The Singapore and Melaka Straits violence, security and diplomacy in the 17th century - Borschberg, Peter (NUS Press, 2010)
The first half of the seventeenth century brought heightened political, commercial and diplomatic activity to the Straits of Singapore and Melaka. The book also offers a look at early modern European mapmaking as a projection of Western power, treaty and alliance making, and the struggle for naval hegemony in the Singapore and Melaka Straits